Assessment of the content of metals and metalloids in the snow cover at the oil production sites (Middle River Ob region) - D. V. Moskovchenko; R. Yu. Pozhitkov; A. A. Tigeev (Лëд и снег, 2023)
This article presents results of investigation of dust load and content of metals and metalloids (MMs) in the snow samples taken at the Vatinskoye oil field (Khanty-Mansi Autonomous District - Yugra). Concentrations of dissolved and suspended forms of MMs in 20 samples collected in March 2021 were determined by the ICP-MS and ICP-AES methods. Eighteen elements (Ag, Ba, Bi, Cd, Cr, Cu, Fe, Hg, Li, Mn, Ni, Pb, Sb, Sn, Sr, Ti, W, and Zn) indicating various sources of emissions were selected for further analysis. Filters with a pore diameter of 0.45 μm were used to separate dissolved and suspended forms. Enrichment of the suspension with chalcophile elements (Ag, Cu, Zn, Sn, Sb, Pb) was noted in the background areas. Calculations of enrichment coefficients (CO) using Li as a reference element demonstrated that Cu, Mn and Ni come from natural sources (rocks and soils), while the others have a mixed natural-anthropogenic origin. It was noted also that the mass fraction of a number of metals (Cr, Cu, Ni, Zn) increases in solid-phase deposits. The metals Zn, Cu and Cr are mainly contained in snow in suspended form, and Ni - both in dissolved and suspended forms. As a result of calculations of the total Cr pollution index, most of the deposit is classified as "low, non-hazardous" pollution areas. The highest concentrations of MMs in the snow were found in the southern part of the deposit, where the main infrastructure facilities and the communications lines are concentrated, including roads, railways and pipelines. They were specified as "average, moderately dangerous" level of pollution. To determine sources of pollution, the factor analysis was applied, and as a result of which two main factors were identified: 1) the background pollution, which is indicative of deposition of Cu, Sn, Sb, Ag; 2) the anthropogenic one, corresponding to high levels of Cr, Ni, Zn. Spatial analysis of the MMs distribution showed that the deposition of Ni, Cr is associated with drilling operations, while Zn - with the presence of transport. The data obtained can be used to understand the processes of atmospheric deposition of potentially toxic metals and metalloids, as well as to assess the quality of the environment at oil and gas fields.